Microscopic morphology and size distribution of PM2.5in Guangzhou urban area in fall 2011 - XD Feng; CB Ming; Liu, H.; Zhang, Y. H.; M* Zheng (China Environmental Science, 2015)
Samples of airborne PM2.5 particles were collected during Fall 2011 from Guangzhou urban area. The morphology and size distribution of individual particles were analyzed by a Scanning Electron Microscopy coupled with Energy Dispersive X-ray Spectrometer(SEM-EDX) and Image Analysis System. Based on the morphology, three typical particles(soot aggregates, minerals, and coal fly ash) and other unknown particles in PM2.5 were identified. Results showed that the number-size distribution of PM2.5, peaking in the range of 0.1~0.2 μm, was dominated by the condensing sub-mode within the accumulation mode where gas phase reaction products were distributed. Both number and volume contribution of three typical particles were on the order of mineral soot aggregate fly ash. Minerals were mainly distributed in range of 0.1~0.3 μm with 41.97% in number percentage. The percentage of minerals in range of 0.1~0.2 μm was as high as 26.42%, which was the major factor influencing the overall size distribution of PM2.5. Size distributions of PM2.5particles were fairly similar during different sampling period(morning, afternoon, evening) as well as before and after raining, but the proportions of particles having sizes less than 0.1 μm were significantly decreased in the evening and after raining.